Hard to get : a novel - Moher, Laura (Big Love From Galway, 2025)
"Andi Salazar's hard work at the local women's shelter makes a big difference in her small town, but at the end of a long day, Andi can't wait to blow off some steam as her sexy, voluptuous bombshell singer persona. Andi burns down the stage with her fiery spirit, catching the eyes of Galway High's popular new math teacher, Kevin Mahoney. After his ex dubbed him as too "vanilla", Kevin's on a mission to find the real version of himself. One look at Andi and he nearly bursts into flame. After colliding in the hallway, their chemistry leads to a hot, sweet hookup that leaves him wanting more. But when their work brings them together again, Andi and Kevin can't stay apart for long. Kevin is the first man Andi feels like she can trust, and conversation with Andi makes Kevin truly enjoy opening up to her. Although friendship may be safer, romance could be everything and more, especially when an unexpected variable changes their lives in the best way possible"--